2015
DOI: 10.1016/j.bbadis.2015.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cereblon by fenofibrate ameliorates alcoholic liver disease by enhancing AMPK

Abstract: Alcohol consumption exacerbates alcoholic liver disease by attenuating the activity of AMP-activated protein kinase (AMPK). AMPK is activated by fenofibrate, a peroxisome proliferator-activated receptor α (PPARα) agonist, and inhibited by direct interaction with cereblon (CRBN), a component of an E3 ubiquitin ligase complex. Based on these preliminary findings, we investigated that CRBN would be up-regulated in the liver by alcohol consumption and that CRBN deficiency would ameliorate hepatic steatosis and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…For instance, a HFD increases CRBN expression at gene and protein levels [43], suggesting that intracellular energy balance is an important regulator of CRBN expression. Another study shows that fenofibrate, a PPARα agonist, attenuates alcohol-induced CRBN overexpression and liver disease [33]. In this study, alcohol treatment increased CRBN gene expression by suppressing the PPARα-dependent pathway, suggesting that PPARα is a negative transcriptional regulator of CRBN.…”
Section: Potential Regulators Of Crbn Expressionsupporting
confidence: 50%
See 1 more Smart Citation
“…For instance, a HFD increases CRBN expression at gene and protein levels [43], suggesting that intracellular energy balance is an important regulator of CRBN expression. Another study shows that fenofibrate, a PPARα agonist, attenuates alcohol-induced CRBN overexpression and liver disease [33]. In this study, alcohol treatment increased CRBN gene expression by suppressing the PPARα-dependent pathway, suggesting that PPARα is a negative transcriptional regulator of CRBN.…”
Section: Potential Regulators Of Crbn Expressionsupporting
confidence: 50%
“…Whereas a HFD enhances lipogenesis and gluconeogenesis in mice with elevated CRBN levels, CRBN KO suppresses HFD-induced lipogenesis and gluconeogenesis. Another recent study demonstrates that CRBNdeficient mice are resistant to alcohol-induced metabolic dysfunction via peroxisome proliferator-activated receptor alpha (PPARα)/AMPK pathway activation [33], suggesting a regulatory role of CRBN in pathological metabolic remodeling of the liver.…”
Section: Obesity Insulin Resistance and Fatty Livermentioning
confidence: 99%
“…Previous studies have shown that CRBN has a significant role in the regulation of metabolic homeostasis and metabolic processes. 22,23 Therefore, we examined the potential role of CRBN in alcohol-mediated regulation of oxidative stress and liver injury using an adenoviral delivery system (Ad-Crbn) and Crbn null mice. Quantitative PCR analysis showed that Ad-Crbn was successfully delivered in mouse livers.…”
Section: Alcohol-mediated Liver Injury Is Altered By the Cb1r-crbn mentioning
confidence: 99%
“…It is highly expressed in the brain and is also present in diverse tissues, including skeletal muscle, kidney, and liver . Our previous studies have demonstrated that disruption of CRBN improves hepatic steatosis and inflammation via AMPK activation in mouse models of nonalcoholic and alcoholic fatty liver diseases . In addition, Ying Yang 1 (YY1) is a multifunctional zinc‐finger transcription factor of the polycomb protein family which can bind to its signature binding motif (CCATNTT) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation